Matching relations in Borges’ la muerte y la brújula: an exercise in linguistic stylistics - Coulthard, Malcolm (Lenguas Modernas, 2017)
This article introduces and exemplifies a pervasive linguistic feature of literary and non-literary texts, the matching relation, and then sets out to demonstrate how matching relations are a basic organising device of the Borges short story. A close examination of the text shows how carefully constructed and worded the original is and how important clues are conveyed through the matching relations. A brief comparison of several translations shows that some of these crucial matching relations are obscured by careles translation.